Melanogenesis of methyl myristate loaded niosomes in B16F10 melanoma cells - Aranya Manosroi (2018)
The objective of this study was to compare the charge effect of methyl myristate loaded in neutral (Brij 72/cholesterol at 7:3), cationic (Brij 72/cholesterol/dimethyl dioctadecyl ammonium bromide at 7:3:0.65) and anionic niosomes (Brij 72/cholesterol/dicetyl phosphate at 7:3:0.65) for physicochemical characteristics, cytotoxicity in fibroblasts and B16F10 melanoma cells as well as melanogenesis induction activity. The maximum loading and percentage entrapment of methyl myristate were 4.5, 90.68±7.95 in neutral; 11.0, 92.54±6.32 in cationic and 0.1% w/w, 74.43±1.86% in anionic niosomes, respectively. All methyl myristate loaded niosomes were in unilamellar structure under transmission electron microscope and in nanosize at initial and after 3-month storage. The percentages of methyl myristate remaining in all niosomes kept at 4±2, 30±2 and 45±2 °C for 3 months were about 82, 74 and 72%, respectively, while the dry free methyl myristate indicated 97.82±1.74, 96.56±2.91 and 91.39±4.32%, respectively. Blank neutral, blank cationic and methyl myristate loaded neutral and cationic niosomes exhibited moderate cytotoxicity in fibroblasts and B16F10 melanoma cells at 56.64±3.19, 59.72±1.51; 73.81±2.86, 82.51±0.20; 47.34±2.13, 52.67±2.78 and 73.20±3.49, 84.34±2.75% cell viability, respectively. Blank anionic and methyl myristate loaded anionic niosomes indicated no cytotoxicity in both cells. Cytotoxic ratio of cell v iability in normal and cancer cells of all niosomes indicated no toxic effect to normal cells. Methyl myristate loaded cationic niosomes demonstrated the highest melanin induction with tyrosinase activity of 1.42 and 1.70 folds of the control and 1.14 and 1.59 folds higher than theophylline, respectively. This study has suggested the potential of methyl myristate loaded cationic niosomes for canities treatment. Copyright © 2013 American Scientific Publishers All rights reserved.